Teacher Education through Drama. CLIL Practice in the Spanish Context - Agata Muszyńska; Carmen Urpí; Alicja Gałązka (Universidad de Navarra, 2017)
The paper is inspired by the increasing educational development of bilingualism and CLIL in Spain and the need to explore new teaching methodologies in initial teacher education in this field. On the basis of other European countries' experience, above all the United Kingdom and Poland, an academic course on drama was designed for Education students taking a degree in Early Childhood, Primary Education and/ or Pedagogy. This consisted of teaching drama theory and practice, providing support with class design, and observing the application during the qualifying phase in educational institutions. As a result, on the one hand, many common characteristics of CLIL and drama were observed. On the other hand, the practice-focused phase proved that drama can stimulate the development of many skills and attitudes pursued in CLIL methodology. We observed that drama, as a form of experiential learning, strengthens the process-focused approach, going beyond the mere instrumental use of theatre techniques. The research results provide guidelines for future teachers about how to fulfil both process- and product-centred educational objectives by means of drama, critical and creative thinking, through the exercise of freedom, enhancing students' participation in a shared learning experience.